Exigências nutricionais de energia e proteína para mantença e ganho de peso de cordeiros da raça Texel - Martins, Andressa Ana (2013)
This study aimed to determine the energetic and protein requirements to gain and maintenance for fitness lamb meat Texel. The experiment was made at the Sheep Laboratory, in the Universidade Federal de Santa Maria (UFSM). It was used 56 Texel lambs, male not castrated, weaned at 50 days of age and housed in individual places (2 m²). The diet consisted of sorghum (Sorghum bicolor (L) Moench), grain of corn (Zea mays L.), soybean (Glycine max L.) and mineral mix, and it was calculated to attend the requirements of crude protein, metabolizable energy and macro minerals recommended by NRC (2007), for a daily gain of 0,200 kg. After 14 days for the animal adaptation to the experimental conditions, 14 lambs were randomly selected and slaughtered. Among the remaining, 24 animals were fed ad libitum and slaughtered at 25, 30, 35 ou 40 kg of body weight (BW), and 12 animals were submitted to two levels of food supply (70 or 55% of ad libitum intake). The slaughter of these last animals was made with those which were fed ad libitum and slaughtered at 40 kg BW. It was formed ten groups of the body components in which were determined the body content of nitrogen, fat and energy. And yet, six lambs were undergone to a digestibility trial with the aim of evaluating the nutritional diet value under the different levels of consumption. The lambs were kept into individual metabolic cages under double 3x3 Latin Square Desing. In the higher level of dietary restriction it was gotten the highest percentage of apparent digestibility and the biggest energy concentration of the diet. The protein concentration in the body free from wool decreased with the increasing of empty body weight (EBW), the fat and energy body concentration increased as the PVC was high. The endogenous nitrogen excretion was 279 mg/kg PV0,75/day, which corresponded to the net requirement protein for maintenance of 1,74 g/kg PV0,75/day, this one corresponds to a metabolizable protein requirement for maintenance of 1,74 g/kg PV0,75/day, considering an efficient utilization equal to 1,0. The net energy requirement for maintenance was 56,49 kcal/kg PV0,75/day and the metabolizable energy of 82 kcal/kg PV0,75/day. The protein requirements and net energy for weight gain of lambs with 25 and 40 kg BW and daily average gain of 250g were 34 g/day and 552 and 664 kcal/day.